Manajemen Kepala Sekolah dalam Meningkatkan Profesionalisme Guru di SMP Plus Ma’arif Nu Pangandaran - Alfi Maulia Rahmah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
The study is intended to describe and further examine how the management of the headmaster and the programs put forth by the principal in an effort to improve the teacher's professionalism and its contributing factors and disruptions. As for this type of research, it is qualitative research with case studies designed by taking in data sources in school and teacher through observation, interview and documentary data collection techniques. The data is analyzed as data reduction, data presentation, drawing conclusions and testing data validity with the source trululating, engineering and time.Research shows that the management of the principal at ma 'aarif nu middle school consists of planning, administration, supervision, and organization. The principal as a manager is acting as a educator, manager, supervisor, motivator, and educator. The principal's management measures are to perform a supervision, provide reward, motivate and encourage further education. The supporting factors of headmaster management in promoting teacher professionalism can be brought about by the teacher's discipline, motivation, self-awareness of the teacher's level of education, tools and infrastructure, and management of the headmaster. Self-discipline is the self-control of consistent self. As stated by danim that self-discipline is realization and independent. Teachers of discipline have strong self-awareness and motivation to perform their duties and functions both in school and in society. As for the lack of time management, at least the honor teachers certification, the teachers' time management and staff less than optimal, some teachers still use RPMS from the previous year and teachers still have not been able to do time between the home and the school environment, so the school work is sometimes slow because of the lack of time.